THE GLOBAL LACTIC ACID MARKET - OKHMAT , OLENA; ZHALDAK, MARYNA; MOKROUSOV, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article analyzes Ukraine’s foreign trade in lactic acid and explores its potential applications in the food, pharmaceutical, medical, and chemical industries. The analysis is based on statistical data from ChemAnalyst and the State Statistics Service of Ukraine. The study found that the largest application of lactic acid is in the production of polylactic acid, driven by the increasing production of biodegradable polymers used for disposable tableware, containers, and food packaging. The food industry ranks second in terms of lactic acid consumption, with applications in fermentation processes, beverage production, and meat and fish processing. The global lactic acid market is characterized by dynamic growth, particularly in regions with developed chemical and food industries. The United States and Europe account for the largest share of the lactic acid market, where lactic acid produced by fermentation is widely used. The rapid growth rate of nearly 9% per year indicates the potential for the market to reach a volume of 7.93 billion by 2032. This growth is underpinned by the availability of a developing raw material base. Additionally, the expanding range of applications for lactic acid is stimulating market growth. An analysis of Ukraine’s foreign trade in lactic acid from 2021 to 2023 reveals a significant imbalance, with imports significantly exceeding exports in both monetary and quantitative terms. Despite the ongoing war in Ukraine, key trading partners have been identified, including China, Uzbekistan, the Netherlands, France, and India. This confirms the relevance and prospects of domestic research in the field of developing technologies for the production and application of lactic acid based on biotechnological principles.